A reversible watermark scheme for 2D vector map based on reversible contrast mapping. Issue 9 (10th December 2012) - Fei, Peng; Li, Chen; Min, Long
ABSTRACT: Reversible watermark is suitable for the hosts with high precision requirement. However, the existed reversible watermark methods are mainly for raster images, and the reversible watermark schemes for vector graphics still have the defects such as low capacity and significant distortion. To counterstrike these situations, a reversible watermark scheme for two‐dimensional vector map based on reversible contrast mapping is proposed. First, the coordinates of the vertices are chosen according to the data precision requirements; then, the data of two‐dimensional vector maps are preprocessed to reduce distortion. After that, the encrypted watermark is embedded into the relative coordinates by using the reversible contrast mapping transform. Experimental results and analysis show that the proposed scheme can achieve higher payload, better reversibility, and invisibility than those of the existed schemes based on difference expansion, discrete cosine transform, and so on. It has great potential in the application of map data authentication and secure communication. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : A reversible watermark scheme for two‐dimensional vector map based on reversible contrast mapping is proposed in this paper. The data of the two‐dimensional vector maps are first preprocessed to reduce distortion. Then, the encrypted watermark is embedded into the relative coordinates by using the reversible contrast mapping. Experimental results and analysis show that it can achieve high payload, good reversibility, and invisibility. It has great potential in the application of map data authentication and secure communication.